The unique role of attachment dimensions and peer drinking in adolescent alcohol use. (15th October 2019) - Anderson, Laura E.; Connor, Jason P.; Voisey, Joanne; Young, Ross McD.; Gullo, Matthew J.
Abstract: Adolescent alcohol use can result in adverse health and social outcomes, including elevated risk of future substance use disorders. Insecure attachment and heavy peer use are both linked to early problematic drinking, but the precise relationship between these variables is poorly understood. Further, mixed findings in prior literature highlight the importance of distinguishing between both dimensions of insecure attachment – anxiety and avoidance. This laboratory-based study investigated whether peer use moderates the association between attachment and laboratory alcohol consumption in a sample of 120 adolescents of legal drinking age (18–21 years). The relationship between attachment and self-reported alcohol use was also investigated. It was hypothesized that both dimensions of insecure attachment would predict greater self-report and laboratory alcohol use, and that the presence of a heavy drinking peer would strengthen this relationship. Results indicated that attachment anxiety, but not avoidance, predicted self-report and laboratory alcohol use. Peer drinking did not moderate this effect. Findings emphasize the importance of investigating both attachment anxiety and avoidance, and suggest that future research should focus on mediating mechanisms between attachment anxiety and alcohol use. Highlights: Insecure attachment dimensions have been implicated in alcohol use. Peer drinking is a robust predictor of alcohol use. We examined interactions of these predictors in an adolescent sample. Attachment anxiety predicted self-reported and actual alcohol use. Peer drinking did not moderate this effect.